Drawing the students’ attention to humanized care: teaching experiences and learning with them - Rolim, Karla Maria Carneiro; Campos, Antonia do Carmo Soares; Cardoso, Maria Vera Lúcia Moreira Leitão; Silva, Raimunda Magalhães da (Rev Rene, 2004)
This is a descriptive study based on a qualitative approach carried out with nursing graduate students together with postgraduate students. Data was collected in a public maternity in Fortaleza-Ce from November 2002 to February 2003. A questionnaire was applied in two phases: theoretical and practical classes with the newborn child in the infirmary. The analysis of the data collected showed that students consider humanization a state of well-being, which should be included in the nursing care procedures. It is necessary to change the current standards of the process of teaching how to care. The methodology used encouraged the students’ participation in the new procedures and improved their learning process.